Hypothalamic-pituitary-gonadal function in men with cirrhosis of the liver. Issue 5 (May 1976) - Mowat, N A; Edwards, C R; Fisher, R; McNeilly, A S; Green, J R; Dawson, A M
Abstract : Hypothalamic-pituitary-gonadal function was studied in 37 cirrhotic males, 25 of whom were alcoholic. Irrespective of aetiology, cirrhotic patients had significantly reduced free testosterone concentrations. Despite low free testosterone concentrations and reduced or absent spermatogenesis, basal levels of luteinizing hormone (LH) and follicle stimulating hormone (FSH) were normal in nearly all patients, suggesting impaired function of the hypothalamic-pituitary-gonadal axis. In 14 cirrhotic men, seven of whom had gynaecomastia, the ability of the pituitary to secrete LH and FSH in response to exogenous gonadotrophin releasing-hormone (LH/FSH-RH) was asssessed. A normal LH response to LH/FSH-RH was obtained in patients without gynaecomastia. An exaggerated LH response was found in four of seven with gynaecomastia, suggesting Leydig cell failure. The Leydig cell response to exogenous gonadotrophin in eight consecutive cirrhotic patients was probably abnormal but difficult to interpret as all but one were within conventionally accepted limits of normality. The patients without gynaecomastia gave a normal or minimally exaggerated FSH response to LH/FSH-RH. Six of seven with gynaecomastia gave a markedly exaggerated response suggesting failure of spermatogenesis, and all tested were either azoospermic of oligospermic. The single patient with a normal FSH response had a normal sperm count. The pituitary cells can therefore respond to LH/RSH-RH and the Leydig cells of the testes show some response to exogenous gonadotrophin. Similar abnormalities in hypothalamic-pituitary-gonadal function have recently been described in patients with normal liver function on chronic oestrogen therapy.